2006
DOI: 10.1080/01140671.2006.9514423
|View full text |Cite
|
Sign up to set email alerts
|

Selenium concentration in wheat (Triticum aestivum) grain as influenced by method, rate, and timing of sodium selenate application

Abstract: Field trials were conducted to identify effective methods of increasing selenium (Se) in wheat (Triticum aestivum) grown on low-Se soils in Canterbury, New Zealand. Various rates (5-20g Se/ha) and methods (soil-applied fertiliser, seed treatment, foliar application at flowering) of applying Se (sodium selenate) were evaluated in autumn-and spring-sown crops on an irrigated site at Wakanui and on a dryland site at Methven. Several Se fertiliser treatments were included to examine the effects of timing of applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
36
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 14 publications
10
36
1
Order By: Relevance
“…However, supplemental Se resulted in much higher grain yield under normal than water deficit conditions. Foliar Se application was observed to be more effective than other Se supply methods and is in agreement with the findings of Curtin et al (2006) who found that foliar application of Se was more effective than soil fertilization in increasing growth and yield of wheat. Literature also confirmed that application of Se increases the growth and yield in rice (Wang et al 2013), lettuce seedlings (Xue et al2001) and soybean (Djanaguiraman, 2004) etc.…”
Section: Yield and Yield Componentssupporting
confidence: 90%
“…However, supplemental Se resulted in much higher grain yield under normal than water deficit conditions. Foliar Se application was observed to be more effective than other Se supply methods and is in agreement with the findings of Curtin et al (2006) who found that foliar application of Se was more effective than soil fertilization in increasing growth and yield of wheat. Literature also confirmed that application of Se increases the growth and yield in rice (Wang et al 2013), lettuce seedlings (Xue et al2001) and soybean (Djanaguiraman, 2004) etc.…”
Section: Yield and Yield Componentssupporting
confidence: 90%
“…The total Se contained in grain was significantly affected by all the three factors; year, Se form and Se dose (Table 5) Results show that foliar selenite and selenate additions can increase Se contents in mature wheat grains up to 3 and 18 times, compared to selenium non-supplemented crops. As Curtin et al (2006) found, selenium content in wheat grain increased from 0.03 mg/kg in the control samples to 0.45 mg/kg when Se was added as selenate at 20 g/ha by using foliar spray.…”
Section: Resultsmentioning
confidence: 57%
“…Although several other parameters could have affected such lower Se concentration in the grain, a very early application does not seem to be the most convenient. Other authors have reported a better Se accumulation when Se was applied at flowering stage (Curtin et al, 2006) or even at grain filling (Chu et al, 2013). However, these studies were conducted in more humid regions or in irrigated crops.…”
Section: Total Se In the Grain And In The Flourmentioning
confidence: 97%
“…Regarding the time of application, many authors (Curtin, Hanson, Lindley, & Butler, 2006;Chu, Yao, Yue, Li, & Zhao, 2013) recommended just one application at stem elongation stage, when the flag leaf ligule/collar is just visible (GS-39 according to the Zadocks scale). That growth stage has been regarded as the most effective one in the later Se accumulation in the grain when several applications moments were evaluated.…”
Section: Introductionmentioning
confidence: 99%